Hydrological Alterations of the Da River by Cascade Reservoir - Y Nhu, Nguyen; Dinh Kha, Dang; Hong Van, Dao Thi; Thuy Linh, Doan Thi (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Large reservoir systems can alter river flow regimes. In the Red River basin, the Da River is the dominant tributary, contributing over 40% of discharge at Son Tay. Since the cascade reservoirs of Hoa Binh (1988), Son La (2010), and Lai Chau (2016) began operation, flow regimes have shifted. This review applies the PRISMA approach and a hydrological indicator framework to synthesize the three decades of evidence. Findings show that wet-season discharge at Son Tay declined from ~83% to 69–72% of annual flow, whereas dry-season contributions rose by 10–20%. Flood peaks decreased by more than 30%, low flows were maintained above 1,500 m³/s, and pronounced hydropeaking occurred near dam outlets. Suspended sediment load dropped by 52–80%, and the center-of-timing of floods shifted later in the wet season. Attribution studies indicate human activities (reservoirs, land-use change) are responsible for 60–70% of discharge alterations, exceeding the 30–40% contribution of ENSO and climate. These results highlight the dual role of reservoirs: enhancing flood control, energy, and water security, while posing challenges for sediment balance, riverine ecology, and sustainable flow management.